Use of Vermicompost and Refugia Plants in Organic Agriculture in Kuluran Village, Kali Tengah, Lamongan - Moch. Arifin; Nony Rahmadiny (Future Science)
Sustainable agriculture is not only limited to eliminating the use of agricultural inputs in the form of inorganic substances but in the form of utilizing local natural resources. The use of vermicompost and refugia plants is an alternative in organic farming. The purpose of this study was to determine the use of vermicomposts and refugia plants as inputs for organic farming in lowland rice. The study was carried out on a paddy pond in the village of Kuluran, Kali Tengah, Lamongan. The study used a randomized block design with treatment giving 20 tons ha-1 kascing and refugia plants on (P0) without chemical fertilizers, (P1) with the addition of 562.5 kg ha-1 NPK, (P2) adding 375.0 kg ha-1 NPK, (P3) addition of 187.5 kg ha-1 of NPK and (P4) addition of 750.0 kg ha-1 of NPK. All treatments were repeated 3 times. The results showed that the application of vermicompost treatment of 20 tons ha-1 and refugia plants without organic fertilizer gave the highest yield at the final plant height (118.61, cm) and the production of wet rice (13.28 tons ha-1).